Pengunkapan Etika Laporan Keuangan Islam di Bank Umum Syariah di Indonesia - Budi Dharma; Amalia Munajah Nasution; Hafyah Yasmita (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to determine the ethics of disclosing Islamic financial reporting at Indonesian Sharia Commercial Banks (BUS) Indonesian. The methods used are qualitative and quantitative methods. The findings show that, in Gus Dur's opinion, the ethics of preparing financial reports from an Islamic perspective to improve the quality of financial reporting indicates whether an action is moral or not based solely on interests, obligations, justice or benevolence. The actions we take must adhere to the values of justice. The justice in question is justice in favor of the parties, in this case both internal and external parties of an entity.